2020
DOI: 10.1111/cen.14318
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of metabolic disorders in patients with bilateral primary aldosteronism than unilateral primary aldosteronism

Abstract: Objective: Metabolic syndrome (MetS) is a frequent clinical condition in hypertension patients and is more frequently reported in primary aldosteronism (PA). This study is aimed at investigating the prevalence of MetS and its components in the two major types of patients with adrenal venous sampling (AVS)-confirmed unilateral PA and bilateral PA. Design and patients: This was a retrospective cross-section study. We analysed metabolic parameters from 169 PA patients subtyped by AVS, including 85 unilateral PA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
(52 reference statements)
2
18
0
Order By: Relevance
“…The strength of our study is the direct use of CT scans to assess the abdominal component, in particular, the SAT and VAT can be measured directly and quantified using the following indexes, area and ratio. Our approach should be more convincing than other previous studies that use weight, BMI, or WC for assessment (16,17).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The strength of our study is the direct use of CT scans to assess the abdominal component, in particular, the SAT and VAT can be measured directly and quantified using the following indexes, area and ratio. Our approach should be more convincing than other previous studies that use weight, BMI, or WC for assessment (16,17).…”
Section: Discussionmentioning
confidence: 91%
“…Whereas, interesting was that recent studies had indicated that patients with APA had higher risk of developing cardiac events among the PA population (27,28). And despite having lower PAC than patients with APA, only those with IHA are more likely to develop MetS (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndrome (MetS) is a frequent clinical condition in hypertensive patients especially in PA patients ( 33 ). In addition, APA and IHA may have different mechanisms to cause Mets ( 34 ). In general, aldosterone excess is often present in obesity and is closely associated with visceral adipose tissue, suggesting its involvement in the pathogenesis of obesity-related hypertension ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, obesity-associated PVAT leads to a change in the profile of the released adipocytokines, resulting in a decreased vasorelaxing effect. It has been reported that obesity-related factors may contribute to the pathogenesis of IHA ( 34 ). Since obesity results in an imbalance between endothelium-derived vasoactive factors favoring vasoconstriction, we expected that positive relationship between FMD and BMI is found in IHA group, as opposed to APA group.…”
Section: Discussionmentioning
confidence: 99%